Enhancing the Psychological Well-Being of Higher Education English Lecturers: A Qualitative Study - Ghafar, Zanyar Nathir (Future Science, 2024)
This study explores the influence of mental health on the instructional approaches employed by higher education English lecturers in the Kurdish region. The primary objective of this study is to find effective techniques that may be implemented to enhance the psychological well-being of these teachers. The qualitative method was used by conducting semi-structured interviews with 5 lecturers at the National Institute of Technology in Kurdistan. The selection of these individuals was crucial in order to get critical insights and perspectives. The results indicate that there is a positive relationship between more significant levels of well-being and instructional practices, resulting in enhanced levels of participation, inspiration, and pleasure. The fundamental qualities that are emphasized are autonomy in teaching, competency, and effectiveness, as well as healthy student interactions. The study findings indicate that using several tactics, such as autonomy assistance, building skills, interaction, acknowledgment and feedback, and a healthy balance between work and life, is a means to enhance the overall well-being of higher education English lecturers. This study is based on a literature review on the topic of teacher well-being, offering valuable insights that may inform pedagogical administrators, staff members, and instructional programs in their efforts to cultivate a conducive atmosphere for professional development and the delivery of successful English language teaching.